Sustainable Community Project Identification and Selection Based on the Experience Gained from Emergency Northern Recovery Project - Sivakumar, S.; Janen, S. (Proceedings of International Conference on Contemporary Management, 2014)
Sri Lankan Northern and Eastern regions were suffered by civil war form past three decade. After Sri Lankan Government announced the victory against civil war, World Bank initiated to rebuilt the Northern region by the project namely “Emergency Northern Recovery Project (ENReP)” With the scope of; supporting the IDPs in the Northern Province to resettle in their place of origin to start their lively hood and allocation 75.5 US $ through 4 components namely Emergency Assistance to IDPs, Work-fare Program (Cash for work), Rehabilitation and Reconstruction of Essential Public and Economic Infrastructure, Project Management Support. This paper focusing on the achievement of the project during the short period of time and the successful selection criteria implemented. 98%, 99%, 86% and 94 % of the respective funds have been utilized by the Project. 6,815 Ha land was brought under cultivation through Emergency Assistance, 44,612 families in 283 GN Divisions were benefitted through Work-fare Program, 653Km rural roads, 9 water supply schemes, 103 irrigation tanks and 462 public buildings have been created and through Rehabilitation and Reconstruction of Essential Public and Economic Infrastructure. 200,000 people directly and more than 0.5 million people indirectly benefited through the project. Rather than 100% of community selection, combination of community selection and direct official selection will be the best method for sub project selection. After the receiving the requirement from the community prioritizing by the official and in cooperates the essential basic items which will benefit the community in the near future should also be added in to the selection to make it sustainable and benefited for the community.
Keywords: Community Contract